2019
DOI: 10.1080/00071668.2019.1652884
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a high-protein DDGS product in broiler chickens: performance, nitrogen-corrected apparent metabolisable energy, and standardised ileal amino acid digestibility

Abstract: 1. New production processes and additional uses for corn co-products have increased the availability of distiller's dried grains with solubles (DDGS) with varying energy and amino acid digestibility, for use in poultry feed. The objective of this study was to determine the performance, N-corrected metabolisable energy (AMEn), and amino acid (AA) digestibility of a 34% CP (as fed) high-protein DDGS (HP-DDGS) included in poultry diets for Cobb 500 broiler chickens. 2. A total of 832 Cobb 500 broilers were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
5
10
0
Order By: Relevance
“…However, the estimated AID of AAs in CDDGS in this study was higher than those previously reported [16]. The SID of AAs for corn, SBM, and CDDGS were within the range reported in previous studies [1,15,17,18]. The SID of the indispensable AAs in corn, SBM, and CDDGS ranged from 91.4% (Thr) to 98.0% (Met), from 93.5% (Thr) to 97.4% (Met), and from 73.5% (Lys) to 89.5% (Leu), respectively.…”
Section: Resultssupporting
confidence: 71%
“…However, the estimated AID of AAs in CDDGS in this study was higher than those previously reported [16]. The SID of AAs for corn, SBM, and CDDGS were within the range reported in previous studies [1,15,17,18]. The SID of the indispensable AAs in corn, SBM, and CDDGS ranged from 91.4% (Thr) to 98.0% (Met), from 93.5% (Thr) to 97.4% (Met), and from 73.5% (Lys) to 89.5% (Leu), respectively.…”
Section: Resultssupporting
confidence: 71%
“…It can be defined as a product obtained after ethanol extraction by distillation from the yeast fermentation, and drying at 75% of the resultant [8]. Including DDGS in poultry diets to replace part of yellow corn and soybean meal have shown positive results in terms of growth performance [9]. The main limitation of using DDGS in monogastrics is the variability of its nutrients content and availability [9].…”
Section: Distillers Dried Grains With Solubles (Ddgs)mentioning
confidence: 99%
“…Including DDGS in poultry diets to replace part of yellow corn and soybean meal have shown positive results in terms of growth performance [9]. The main limitation of using DDGS in monogastrics is the variability of its nutrients content and availability [9]. This is due to the variation of growing conditions, ethanol production method and oil extraction.…”
Section: Distillers Dried Grains With Solubles (Ddgs)mentioning
confidence: 99%
“…When converted to a dry matter basis, crude protein (CP) ranged from 26.0% to 31.7%, fat from 9.1% to 14.1%, ash from 3.7% to 8.1%, acid detergent fiber (ADF) from 11.4% to 20.8%, and neutral detergent fiber (NDF) from 33.1 to 43.9%, with average values for protein, oil, ash, total carbohydrate, ADF, and NDF of 29.7%, 10.7%, 5.3%, 54.3%, 15.9%, and 38.8%, respectively, and average dry matter of 90.5% (Liu, 2011). In particular, the nutritional values of DDGS were primarily related to the contents of CP, amino acids (AA), minerals (Ca, Mg, P, and K), and dietary fiber in DDGS (Fries‐Craft & Bobeck, 2019). Under the same fermentation conditions, previous studies showed that the CP content of maize‐DDGS was lower than that of wheat‐DDGS (Böttger & Südekum, 2017b; De Boever et al, 2014).…”
Section: Introductionmentioning
confidence: 99%